Revealing a Novel Landscape of the Association Between Blood Lipid Levels and Alzheimer's Disease: A Meta-Analysis of a Case-Control Study - Tang, Qianyun; Wang, Fengling; Yang, Jingjing; Peng, Hua; Li, Yu; Li, Bin; Wang, Shuhong (Frontiers in Aging Neuroscience, 2020)
Objectives: Blood lipid profiles have been ambiguously reported as biomarkers of AD in recent years. This study was conducted to evaluate the correlation between blood lipid levels and AD in later-life and to explore the effectiveness and reliability of blood lipid profiles as biomarkers of AD. Methods: Databases searching was conducted in using PubMed, EMBASE, the Cochrane Library and Medline. This study was designed in accordance with the Meta-analysis of Observational Studies in Epidemiology (MOOSE) criteria. Review Manager 5.3 (RevMan 5.3) software was adopted to perform meta-analysis evaluating the standard mean difference (SMD) with its 95% confidence intervals (CI). Results: A total of 5286 participants were investigated after they were screened according to the inclusion criteria. Meta-analysis results demonstrated that total cholesterols (TC) level was significantly associated with AD in late-life (SMD = 0.17, 95% CI: [0.01, 0.32], p = 0.03), especially in subgroup under 70 years old (SMD: 0.45, 95% CI: [0.11, 0.79], p = 0.01) and the subgroup of Western population (SMD: 0.29, 95% CI: [0.04, 0.53], p = 0.02). In the subgroup under 70 years old, the high-density lipoprotein cholesterol (HDL-C) level (SMD = -0.50, 95% CI: [-0.76, -0.25], p=0.0001) and the low-density lipoprotein cholesterol (LDL-C) level (SMD = 0.59, 95% CI: [0.02, 1.16], p = 0.04)in the AD group were significantly lower and higher than in the control group, respectively. In the subgroup with a sample size larger than 100 subjects, the LDL-C level was significantly higher in AD patients than in the control elderly group (SMD = 0.31, 95% CI: [0.05, 0.56], p = 0.02). There was no significant association between triglyceride (TG) levels and AD in later-life (SMD = -0.00, 95% CI: [-0.12, 0.12], p = 1.00). Conclusion: TC can be a new predictive biomarker of AD or cognitive decline in later-life. A higher HDL-C level is proven to be correlated with better cognitive function in elderly people. LDL-C level has been found to have a negative association with cognition in elderly people aged 60–70 years old. A further comprehensive study will be necessary in the future.